Green Mussel Shells as Liquid Organic Fertilizer (CARAJA): Efforts to Utilize Local Potential in Banyu Urip Village Gresik - Fardlillah, Qonita; Al Abror, Mohammad Zakky; Al Farobi, Muhammad Abduh (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
Banyu Urip Village is one of the villages located in the coastal area of Ujung Pangkah District, Gresik Regency. The local potential of Banyu Urip Village is green mussels, which are a result of the sea catch of fishermen in the local village. This potential is also a problem due to the accumulation of wasted green mussel shell waste that has not been managed optimally. With this problem, the community service team carried out community service activities aimed at providing alternative solutions as well as community empowerment. The method used in the community service activity of making green shell liquid organic fertilizer "CARAJA" is Participatory Action Research (PAR) with subjects of ± 25 people. The community service activities include 4 stages, namely 1) observation with partners, 2) socialization related to the management of green mussel shells, 3) training in making "CARAJA" liquid organic fertilizer and 4) experiments/trials on the use of liquid organic fertilizer on the growth of mustard seedlings. The results of the community service analysis have shown changes in mustard green plant height when using liquid organic fertilizer, and local communities become knowledgeable and skilled in participating in various stages starting from observation, socialization, and training to experiments on the use of liquid organic fertilizer made from green mussel shell powder (CARAJA). In the final stage, with the existence of experiments/trials, additional findings were added to strengthen the fact that the liquid organic fertilizer "CARAJA" can be managed into a product that has a selling value and shows a significant influence in increasing the growth of mustard greens (Brassica Juncea) and optimizing the management of local potential in the village.